Aplikasi Persediaan Barang Habis Pakai Pada Rumah Sakit Umum Daerah Prabumulih Berbasis Website - Ningsih Aryani, Ningsih Aryani; Cristian, Andi; Barnianto, Ahmad (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2023)
The Consumables Inventory Application is an application that is used to input inventory data into databases, so that there are no errors in input, output and making reports based on the desired data. The problem that occurs in the inventory system that is currently running is that for processing data on incoming and outgoing goods, it still uses stock cards for each category and at the time of reporting it still uses ledger records, so it experiences difficulties in calculating goods and getting the information provided is not appropriate. with the availability of goods. The purpose of this study is to make a Consumables Inventory Application, which can manage incoming and outgoing goods and calculate stock of goods using the waterfall method and implement the Consumables Inventory Application at the Hospital. The results of this study are an effective and efficient application, so that the purchasing process products to suppliers can be more accurate, search data faster, and help the head of the warehouse in the decision making process.